Bibliometric Review Analysis of Academic Outcomes of Flipped Classroom in Physics Education Before and During Covid-19 (Jurnal Pendidikan Fisika, 2023)
The pedagogical approach known as the flipped classroom has gained significant popularity in both higher education and high school settings in recent years. This article aims to provide a comprehensive explanation regarding the comparison of flipped classroom academic results in physics education before and during the Covid-19 pandemic. The method used here was bibliometric-based literacy analysis using Publish or Perish (PoP) software and the VOSviewer application, which is focused on the keyword "Flipped classroom in physics" during the last three years before the Covid-19 pandemic (2017 - 2019) and the last three years during the Covid-19 pandemic (2020 – 2022). According to the findings of bibliometric analysis and systematic reviews of articles, the following flipped classroom academic outcomes in physics education were most frequently studied before the Covid-19 pandemic: 1) academic achievement, 2) motivation, 3) students' engagement, 4) students' performance, 5) knowledge acquisition, 6) interest in learning, 7) problem-solving skills, 8) self-efficacy, 9) conceptual understanding, and 10) attitude. Meanwhile, there are eight categories of outcomes in 2020-2021: 1) motivation, 2) academic achievement, 3) student experience, 4) student engagement, 5) conceptual understanding, 6) self-efficacy, 7) process skills, and 8) critical thinking. This study concludes that the academic outcome of flipped classroom research in physics education before the pandemic was more than during the Covid-19 pandemic, and in 6 past years, most research has focused on the effect of flipped classrooms on academic achievement, motivation, conceptual understanding, and self-efficacy compared to other academic outcomes such as scientific reasoning or creative thinking.